Using the five-factor questionnaire to study the personality of a specialist-cynologist of the security agencies of the Russian Federation - Е. А. Kusakina (Вестник университета)
The article presents the results of using the Russian-language version of the “Big Five” personality questionnaire, in which personality is considered as a structure consisting of 5 factors, including many secondary factors. The subject of the study are psychological characteristics of the personality of dog handlers of law enforcement agencies of the Russian Federation (hereinafter referred to as RF) at various stages of professionalisation. The author emphasises the relevance of studying and further psychological support of the professional development of dog handlers, with consideration to the fact that specifics of their service and professional activities in order to ensure the security of the country have no analogues and are unique. The results of a focused interview with experienced dog handlers with extensive experience in service cynology have formed the basis for constructing a psychograph for a specialist in the profile in question. Using the “Big Five” methodology, it is possible to identify the characteristic features of cadets studying in the field of training “Animal Science”, profile “Cynology”, and employees of canine services of the law enforcement agencies of the RF. The author correlates the results obtained and notes the correspondence of the psychological qualities of both groups of respondents to the professionally oriented qualities presented in the psychograph of a specialist dog handler of the law enforcement agencies of the RF. The five-factor questionnaire adapted by A.B. Khromov adequately describes the psychological characteristics of an individual and can be used in the study of various aspects of its professional development.